Compliance with Blood Glucose Control and the Risk of Diabetic Ulcers in Patients with Diabetes Mellitus - Irwansyah, Irwansyah; Sultan, Sultan; Rahmani, Siti; Gairi, Indar; Ohorella, Fadjriah (Sarana Ilmu Indonesia (salnesia), 2025)
Diabetic foot ulcers and blood glucose control are critical aspects of managing Diabetes Mellitus. This study aimed to analyze the relationship between the level of compliance with blood glucose control and the risk of diabetic foot ulcers in patients with Type II Diabetes Mellitus. A quantitative method with a cross-sectional design was employed. A total of 120 subjekts were selected proportionally from a population of 280 individuals in the working area of Bangkala Health Center, Makassar City, based on inclusion and exclusion criteria. A purposive sampling technique was used, and data were collected through a structured questionnaire. The data were analyzed using thechi-square test. The results showed that out of 66 subjekts who were compliant with blood glucose control, 52 were not at risk of developing diabetic foot ulcers, while 14 were at risk. Conversely, among the 54 non-compliant subjekts, 36 were at risk of developing diabetic ulcers, while 11 were not. Bivariate analysis revealed a p-value of 0.000,indicating a statistically significant relationship between the level of compliance with blood glucose control and the risk of diabetic foot ulcers. These findings support the hypothesis that effective blood glucose control significantly reduces the risk of diabetic foot ulcers in patients with Type II Diabetes Mellitus.